Gangguan Pola Napas Tidak Efektif Pada Pasien Acute Myocard Infark (AMI) - Vera Budi Nurani; Yuyun Setyorini; Akhmad Rifai (Interest : Jurnal Ilmu Kesehatan, 2018)
Background: Acute Myocard Infarction (AMI) is the death of cardiac muscle cells due to long-lasting ischemia due to grafting in the coronary arteries. One of the nursing interventions is giving proper oxygen because it affects the condition of the patient who is short of breath. The aim of this study was to describe nursing care in patients with Acute Myocard Infarction (AMI) with impaired breathing disorder. Methods: This research uses data analysis method that is comparing the result criteria achieved from two patients of Acute Myocard Infarction (AMI) who experienced ineffective breathing disorder and then compared with case study journal or other sources. Result: Based on interview and observation it is concluded that with the same nursing diagnoses and implementation there are differences in outcomes and responses between the intervention group and the control group. Suggestion: Suggestions put forward in this study is the need to pay attention to accuracy in conducting assessment to maximize data to determine the priority problems that occur in patients and interventions based ONEC (Observation, Nursing Treatment, Education, Collaboration).